Fluorine-free environment-friendly ceramic non-stick coating and preparation method thereof

CN122917575APending Publication Date: 2026-10-16JIANGSU FAYIN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611015902.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本发明提供了一种无氟环保型陶瓷不粘涂料及其制备方法,解决了现有无氟环保型陶瓷不粘涂料普遍存在涂膜干烧耐磨衰减快,不粘持久性不足,且涂膜孔隙多,导致水、油接触角下降,食物残渣易粘附的问题

Benefits of technology

[0028](1) In the technical solution of the present invention, zinc powder is adhered to the surface of nano-zirconia by sodium carboxymethyl cellulose and then acidified to obtain modified nano-zirconia. On the one hand, core-shell nanoparticles with zirconia as the core and zinc powder as the shell are formed, realizing the composite of wear-resistant zirconia and anti-corrosion zinc powder particles. The two phases are uniformly dispersed in the coating, taking into account both high wear resistance and long-term anti-corrosion performance. Moreover, the zinc powder is attached to the zirconia skeleton by sodium carboxymethyl cellulose and is not easy to fall off during friction, thus maintaining the anti-corrosion effect for a long time. On the other hand, pores are formed in the zinc powder layer on the nano-oxidation surface loaded with zinc powder, which can form a pore structure on the surface of the zinc powder shell layer, increasing the contact area between the modified filler and the coating matrix. The modified filler can form a mechanical interlock with the coating matrix, so that the modified filler is uniformly and tightly dispersed in the coating, avoiding the sedimentation of the modified filler and affecting the wear resistance, non-stickiness and anti-corrosion performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of ceramic coating, and discloses a fluorine-free environment-friendly ceramic non-stick coating and a preparation method thereof, which comprises the following raw materials in parts by mass: 50-60 parts of silica sol, 25-35 parts of methyltrimethoxysilane, 10-15 parts of water-based silicone modified acrylic resin, 10-15 parts of modified filler, 3-8 parts of hydroxyl silicone oil, 5-10 parts of pigment and filler, 30-40 parts of deionized water, 1-2 parts of dispersant and 1-2 parts of formic acid. The silica sol, the methyltrimethoxysilane, the water-based silicone modified acrylic resin, the modified filler, the pigment and filler, the hydroxyl silicone oil, the dispersant and the deionized water are mixed, ground and filtered, then mixed with the formic acid, and subjected to a curing reaction to obtain the fluorine-free environment-friendly ceramic non-stick coating, which has excellent wear resistance, non-stickness, corrosion resistance and hardness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic coating technology, specifically to a fluorine-free environmentally friendly non-stick ceramic coating and its preparation method. Background Technology

[0002] Since its invention, fluorinated non-stick coatings have been widely used in non-stick coatings. However, they have a high curing temperature (400℃), low coating hardness, are easily scratched, and have a short lifespan. Furthermore, they release harmful decomposition products at high temperatures (above 260℃). With increasing environmental awareness and the gradual implementation of safety and hygiene standards, the research and development of fluorine-free environmentally friendly ceramic non-stick coatings has regained importance. Compared to fluorinated non-stick coatings, ceramic non-stick coatings have abundant raw material sources, low VOC content, lower curing temperature (saving energy), do not produce toxic or harmful substances during manufacturing and use (making them healthy and environmentally friendly), and offer high hardness, scratch resistance, long service life, and resource conservation.

[0003] Traditional non-stick coatings generally use polytetrafluoroethylene fluorinated resin, which releases toxic fluorine gas at high temperatures, posing a food safety hazard. Existing fluorine-free environmentally friendly ceramic non-stick coatings generally suffer from rapid wear-resistance degradation after dry burning, insufficient non-stick durability, and numerous pores in the coating, resulting in a decrease in the water and oil contact angle and easy adhesion of food residue. Summary of the Invention

[0004] This invention provides a fluorine-free environmentally friendly ceramic non-stick coating and its preparation method, which solves the problems of rapid wear resistance decay, insufficient non-stick durability, and numerous pores in existing fluorine-free environmentally friendly ceramic non-stick coatings, which lead to a decrease in the water and oil contact angle and easy adhesion of food residue.

[0005] The technical solution of this invention:

[0006] A fluorine-free, environmentally friendly ceramic non-stick coating comprises the following raw materials in parts by weight: 50-60 parts silica sol, 25-35 parts methyltrimethoxysilane, 10-15 parts waterborne organosilicon-modified acrylic resin, 10-15 parts modified filler, 3-8 parts hydroxyl silicone oil, 5-10 parts pigments and fillers, 30-40 parts deionized water, 1-2 parts dispersant, and 1-2 parts formic acid;

[0007] The modified filler is obtained by surface treatment of modified nano-zirconia with a silane coupling agent, followed by mixing with silica-titanium dioxide sol;

[0008] The modified nano-zirconia is obtained by adhering zinc powder to the surface of nano-zirconia with sodium carboxymethyl cellulose and then acidifying it.

[0009] A method for preparing a fluorine-free, environmentally friendly ceramic non-stick coating includes the following preparation steps:

[0010] S1. Mix silica sol, methyltrimethoxysilane, waterborne organosilicon-modified acrylic resin, modified filler, pigments and fillers, hydroxyl silicone oil, dispersant and deionized water, grind on a grinder, filter, and obtain component A;

[0011] S2. Mix component A and formic acid, and carry out a curing reaction at 10-30℃ and 120-180r / min for 6-10h to obtain a fluorine-free environmentally friendly ceramic non-stick coating.

[0012] Furthermore, the pigments and fillers are any one of titanium dioxide, iron oxide black, carbon black, and copper chromium black.

[0013] Furthermore, the dispersant is an aqueous dispersant, specifically dispersant BYK-2012.

[0014] Furthermore, the water-based silicone-modified acrylic resin has a viscosity of 3500-4000S.

[0015] Furthermore, the modified filler is specifically prepared by the following steps:

[0016] A1. Mix zinc powder, nano-zirconia and sodium carboxymethyl cellulose, stir at 1000-1200 r / min for 30-40 min, heat to 300-310℃, continue stirring for 20-30 min, cool to room temperature, wash and dry to obtain zinc powder-loaded nano-zirconia;

[0017] A2. Zinc-loaded nano-zirconia was placed in a phosphate solution with a pH of 3-4 and ultrasonically treated at 40-50 kHz for 10-15 min. After filtration, washing, and drying, modified nano-zirconia was obtained.

[0018] A3. Add the modified nano-zirconia to deionized water and ethanol, stir until homogeneous, add silane coupling agent, stir until the reaction is complete, filter, wash and dry to obtain silanized modified nano-zirconia.

[0019] A4. It is prepared by mixing silica-titanium dioxide sol and silanized modified nano-zirconia in a mass ratio of 1:(0.5-0.8).

[0020] Furthermore, in the A1 reaction process described above, sodium carboxymethyl cellulose acts as a binder, exhibiting high adhesion properties, which enables zinc powder to be uniformly adhered to the surface of nano-zirconia, resulting in zinc powder-loaded nano-zirconia.

[0021] Furthermore, in the above A2 reaction process, the zinc powder-loaded nano-oxidation is etched by phosphate solution and activated by phosphate, which can cause local dissolution at the grain boundaries and defects on the zinc powder surface, precipitate zinc ions and generate hydrated zinc phosphate microcrystals at the interface. After ultrasonic treatment to remove corrosion products, pores are formed in the zinc powder layer on the surface of the zinc powder-loaded nano-oxidation, thus obtaining modified nano-zirconia.

[0022] Furthermore, during the A3 reaction process described above, the hydroxyl groups generated by the hydrolysis of the silane coupling agent can chemically bond with the hydroxyl groups contained on the surface of the modified nano-zirconia, thereby grafting the silane coupling agent onto the surface of the modified nano-zirconia and obtaining silanized modified nano-zirconia.

[0023] Furthermore, during the A4 reaction described above, tetraethyl orthosilicate and tetrabutyl titanate hydrolyze to form silica sol and titanium dioxide sol, respectively. The silica sol and titanium dioxide sol are bonded together by chemical bonds to form a cross-linked network structure of silica-titanium dioxide sol. Moreover, the polar functional groups contained in the silanized modified nano-zirconia allow the silanized modified nano-zirconia to be embedded in the silica-titanium dioxide sol system as a modified filler.

[0024] Further, in step A1, the mass ratio of zinc powder, nano-zirconia, and carboxymethyl cellulose is (0.1-0.3):(1-1.2):(0.01-0.02).

[0025] Further, in step A2, the mass ratio of the zinc-loaded nano-zirconia to the phosphate solution is 1:(7-8).

[0026] Further, in step A3, the mass ratio of the modified nano-zirconia, deionized water, ethanol and silane coupling agent is (2.5-2.7):(30-40):(90-100):(0.8-1).

[0027] The present invention has the following beneficial effects:

[0028] (1) In the technical solution of the present invention, zinc powder is adhered to the surface of nano-zirconia by sodium carboxymethyl cellulose and then acidified to obtain modified nano-zirconia. On the one hand, core-shell nanoparticles with zirconia as the core and zinc powder as the shell are formed, realizing the composite of wear-resistant zirconia and anti-corrosion zinc powder particles. The two phases are uniformly dispersed in the coating, taking into account both high wear resistance and long-term anti-corrosion performance. Moreover, the zinc powder is attached to the zirconia skeleton by sodium carboxymethyl cellulose and is not easy to fall off during friction, thus maintaining the anti-corrosion effect for a long time. On the other hand, pores are formed in the zinc powder layer on the nano-oxidation surface loaded with zinc powder, which can form a pore structure on the surface of the zinc powder shell layer, increasing the contact area between the modified filler and the coating matrix. The modified filler can form a mechanical interlock with the coating matrix, so that the modified filler is uniformly and tightly dispersed in the coating, avoiding the sedimentation of the modified filler and affecting the wear resistance, non-stickiness and anti-corrosion performance of the coating.

[0029] (2) In the technical solution of the present invention, a silane coupling agent is grafted onto the surface of the modified nano-zirconia to obtain silanized modified nano-zirconia. An organosilicon group is attached to the outer layer of the modified nano-zirconia to form an inorganic-organic interface layer, which is beneficial for the modified nano-zirconia to be embedded into the silica-titanium dioxide sol system, further improving the dispersibility of the modified nano-zirconia in the coating, and improving the wear resistance, non-stickiness and anti-corrosion performance of the coating.

[0030] (3) In the technical solution of the present invention, silanized modified nano-zirconia is embedded in the silica-titanium dioxide sol system as a modified filler. On the one hand, the silica-titanium dioxide sol can form a three-dimensional inorganic network with the coating matrix, which can reduce the internal stress of the coating film and improve the hardness of the coating film. The coating matrix can penetrate into the formed three-dimensional inorganic network structure, so that the modified filler and the coating form a mechanical interlock, which improves the interfacial bonding strength between the modified filler and the coating matrix. During friction, the filler is less likely to debond or fall off, which improves the wear resistance, non-stickiness, corrosion resistance and hardness of the coating. On the other hand, the silica-titanium dioxide sol in the modified filler undergoes further condensation during the sintering process to form a continuous and integrated inorganic ceramic network, which further improves the crack resistance of the coating. The formed coating has high density, which improves the wear resistance, non-stickiness, corrosion resistance and hardness of the coating.

[0031] (4) In the technical solution of the present invention, silica sol, methyltrimethoxysilane, waterborne organosilicon modified acrylic resin, modified filler, pigments, hydroxyl silicone oil, dispersant and deionized water are mixed, ground and filtered, and then mixed with formic acid to carry out a curing reaction to obtain a fluorine-free environmentally friendly ceramic non-stick coating with excellent wear resistance, non-stick properties, corrosion resistance and hardness. Detailed Implementation

[0032] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0033] The raw materials used in the embodiments of this invention are shown below, and all reagents used are analytical grade.

[0034] The silica sol is model Bindzil 9950, pH=9, particle size 100nm, solid content 50%, and is manufactured by AkzoNobel.

[0035] The hydroxyl silicone oil, product number 768075, has a kinematic viscosity of 50,000 cSt and was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0036] The water-based silicone-modified acrylic resin, with a viscosity of 3500-4000S and model number S-611, was purchased from Greenlink (Jining) Chemical Technology Co., Ltd.

[0037] The pigment and filler are titanium dioxide, and the dispersant is an aqueous dispersant, namely dispersant BYK-2012.

[0038] The silane coupling agent is KH560 (3-glycidoxypropyltrimethoxysilane).

[0039] Sodium carboxymethyl cellulose, product number C6332, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0040] The nano-zirconia particles have a diameter of 60 nm.

[0041] The zinc powder, with product number LF-Zn-30, has a particle size of 30nm and a purity of 99.9%, and was purchased from Shanghai Liquan Nanomaterials Co., Ltd.

[0042] The silica sol specifically includes the following steps: adding tetraethyl orthosilicate to ethanol and deionized water, stirring at 60°C for 1.5 hours, cooling to room temperature, adding hydrochloric acid to adjust the pH to 2.5, and continuing to stir for 24 hours to obtain silica sol; the mass ratio of tetraethyl orthosilicate, ethanol, and deionized water is 20:40:10.

[0043] The titanium dioxide sol specifically includes the following steps: tetrabutyl titanate is added to ethanol and deionized water, stirred at 45°C for 1.5 h, cooled to room temperature, hydrochloric acid is added to adjust the pH to 2.5, and stirring is continued for 24 h to obtain titanium dioxide sol; the mass ratio of tetrabutyl titanate, ethanol and deionized water is 15:35:10.

[0044] Example 1

[0045] A fluorine-free environmentally friendly ceramic non-stick coating comprises the following raw materials in parts by weight: 50 parts silica sol, 25 parts methyltrimethoxysilane, 10 parts water-based organosilicon-modified acrylic resin, 10 parts modified filler, 3 parts hydroxyl silicone oil, 5 parts titanium dioxide, 30 parts deionized water, 1 part dispersant BYK-2012, and 1 part formic acid.

[0046] A method for preparing a fluorine-free, environmentally friendly ceramic non-stick coating includes the following preparation steps:

[0047] S1. Mix silica sol, methyltrimethoxysilane, waterborne organosilicon-modified acrylic resin, modified filler, titanium dioxide, hydroxyl silicone oil, dispersant BYK-2012 and deionized water, grind on a grinder, filter, and obtain component A;

[0048] S2. Mix component A and formic acid, and perform a curing reaction at 10℃ and 120r / min for 6h to obtain a fluorine-free environmentally friendly ceramic non-stick coating.

[0049] The modified filler is prepared by the following steps:

[0050] A1. Zinc powder, nano-zirconia, and sodium carboxymethyl cellulose were mixed and stirred at 1000 r / min for 30 min. The mixture was then heated to 300℃ and stirred for another 20 min. After cooling to room temperature, the mixture was washed three times with deionized water and dried in an oven at 70℃ for 30 min to obtain zinc powder-loaded nano-zirconia. The mass ratio of zinc powder, nano-zirconia, and carboxymethyl cellulose was 0.1:1:0.01.

[0051] A2. Zinc-loaded nano-zirconia was placed in a phosphate solution with a pH of 3 and sonicated at 40 kHz for 10 min. After filtration, it was washed with deionized water until the pH of the washing solution was neutral and dried in an oven at 80 ℃ for 30 min to obtain modified nano-zirconia. The mass ratio of zinc-loaded nano-zirconia to phosphate solution was 1:7.

[0052] A3. Modified nano-zirconia was added to deionized water and ethanol, stirred evenly, KH560 was added, and the mixture was stirred and reacted at 70℃ for 2 hours. After filtration, the mixture was washed three times with ethanol and three times with deionized water, and dried in an oven at 70℃ for 20 minutes to obtain silanized modified nano-zirconia. The mass ratio of modified nano-zirconia, deionized water, ethanol and KH560 was 2.5:30:90:0.8.

[0053] A4. It is prepared by mixing silica-titanium dioxide sol and silanized modified nano-zirconia at a mass ratio of 1:0.5.

[0054] Example 2

[0055] A fluorine-free, environmentally friendly ceramic non-stick coating comprises the following raw materials in parts by weight: 55 parts silica sol, 30 parts methyltrimethoxysilane, 13 parts water-based organosilicon-modified acrylic resin, 13 parts modified filler, 6 parts hydroxyl silicone oil, 8 parts titanium dioxide, 35 parts deionized water, 1.5 parts dispersant BYK-2012, and 1.5 parts formic acid;

[0056] A method for preparing a fluorine-free, environmentally friendly ceramic non-stick coating includes the following preparation steps:

[0057] S1. Mix silica sol, methyltrimethoxysilane, waterborne organosilicon-modified acrylic resin, modified filler, titanium dioxide, hydroxyl silicone oil, dispersant BYK-2012 and deionized water, grind on a grinder, filter, and obtain component A;

[0058] S2. Mix component A and formic acid, and carry out a curing reaction at 20℃ and 160r / min for 8 hours to obtain a fluorine-free environmentally friendly ceramic non-stick coating.

[0059] The modified filler is prepared by the following steps:

[0060] A1. Zinc powder, nano-zirconia, and sodium carboxymethyl cellulose were mixed and stirred at 1100 r / min for 35 min. The mixture was then heated to 305℃ and stirred for another 25 min. After cooling to room temperature, the mixture was washed three times with deionized water and dried in an oven at 70℃ for 30 min to obtain zinc powder-loaded nano-zirconia. The mass ratio of zinc powder, nano-zirconia, and carboxymethyl cellulose was 0.2:1.1:0.015.

[0061] A2. Zinc-loaded nano-zirconia was placed in a phosphate solution with a pH of 3.5 and sonicated at 45 kHz for 13 min. After filtration, it was washed with deionized water until the pH of the washing solution was neutral. It was then dried in an oven at 80 ℃ for 30 min to obtain modified nano-zirconia. The mass ratio of zinc-loaded nano-zirconia to phosphate solution was 1:7.5.

[0062] A3. Modified nano-zirconia was added to deionized water and ethanol, stirred evenly, KH560 was added, and the mixture was stirred and reacted at 70℃ for 2 hours. After filtration, the mixture was washed three times with ethanol and three times with deionized water, and dried in an oven at 70℃ for 20 minutes to obtain silanized modified nano-zirconia. The mass ratio of modified nano-zirconia, deionized water, ethanol and KH560 was 2.6:35:95:0.9.

[0063] A4. It is prepared by mixing silica-titanium dioxide sol and silanized modified nano-zirconia in a mass ratio of 1:(0.5-0.8).

[0064] Example 3

[0065] A fluorine-free environmentally friendly ceramic non-stick coating comprises the following raw materials in parts by weight: 60 parts silica sol, 35 parts methyltrimethoxysilane, 15 parts water-based organosilicon-modified acrylic resin, 15 parts modified filler, 8 parts hydroxyl silicone oil, 10 parts titanium dioxide, 40 parts deionized water, 2 parts dispersant BYK-2012, and 2 parts formic acid.

[0066] A method for preparing a fluorine-free, environmentally friendly ceramic non-stick coating includes the following preparation steps:

[0067] S1. Mix silica sol, methyltrimethoxysilane, waterborne organosilicon-modified acrylic resin, modified filler, titanium dioxide, hydroxyl silicone oil, dispersant BYK-2012 and deionized water, grind on a grinder, filter, and obtain component A;

[0068] S2. Mix component A and formic acid, and carry out a curing reaction at 30℃ and 180r / min for 10h to obtain a fluorine-free environmentally friendly ceramic non-stick coating.

[0069] The modified filler is prepared by the following steps:

[0070] A1. Zinc powder, nano-zirconia, and sodium carboxymethyl cellulose were mixed and stirred at 1200 r / min for 40 min. The mixture was then heated to 310℃ and stirred for another 30 min. After cooling to room temperature, the mixture was washed three times with deionized water and dried in an oven at 70℃ for 30 min to obtain zinc powder-loaded nano-zirconia. The mass ratio of zinc powder, nano-zirconia, and carboxymethyl cellulose was 0.3:1.2:0.02.

[0071] A2. Zinc-loaded nano-zirconia was placed in a phosphate solution with a pH of 3-4 and sonicated at 50 kHz for 15 min. After filtration, it was washed with deionized water until the pH of the washing solution was neutral and dried in an oven at 80 ℃ for 30 min to obtain modified nano-zirconia. The mass ratio of zinc-loaded nano-zirconia to phosphate solution was 1:8.

[0072] A3. Modified nano-zirconia was added to deionized water and ethanol, stirred evenly, KH560 was added, and the mixture was stirred and reacted at 70℃ for 2 hours. After filtration, the mixture was washed three times with ethanol and three times with deionized water, and dried in an oven at 70℃ for 20 minutes to obtain silanized modified nano-zirconia. The mass ratio of modified nano-zirconia, deionized water, ethanol and KH560 was 2.7:40:100:1.

[0073] A4. It is prepared by mixing silica-titanium dioxide sol and silanized modified nano-zirconia at a mass ratio of 1:0.8.

[0074] Comparative Example 1

[0075] The only difference between this comparative example and Example 3 is the preparation of the modified filler, as detailed below:

[0076] The modified filler is prepared by the following steps:

[0077] A1. Place nano-zirconia in a phosphate solution with pH 3-4, sonicate at 50 kHz for 15 min, filter, wash with deionized water until the pH of the washing solution is neutral, and dry in an oven at 80 ℃ for 30 min to obtain modified nano-zirconia; the mass ratio of nano-zirconia to phosphate solution is 1:8.

[0078] A2. Modified nano-zirconia was added to deionized water and ethanol, stirred evenly, KH560 was added, and the mixture was stirred and reacted at 70℃ for 2 hours. After filtration, the mixture was washed three times with ethanol and three times with deionized water, and dried in an oven at 70℃ for 20 minutes to obtain silanized modified nano-zirconia. The mass ratio of modified nano-zirconia, deionized water, ethanol and KH560 was 2.7:40:100:1.

[0079] A3. It is prepared by mixing silica-titanium dioxide sol and silanized modified nano-zirconia at a mass ratio of 1:0.8.

[0080] Comparative Example 2

[0081] The only difference between this comparative example and Example 3 is the preparation of the modified filler, as detailed below:

[0082] The modified filler is prepared by the following steps:

[0083] A1. Zinc powder was placed in a phosphate solution with a pH of 3-4 and ultrasonically treated at 50 kHz for 15 min. After filtration, it was washed with deionized water until the pH of the washing solution was neutral. It was then dried in an oven at 80 ℃ for 30 min to obtain modified zinc powder. The mass ratio of zinc powder to phosphate solution was 1:8.

[0084] A3. Add the modified zinc powder to deionized water and ethanol, stir well, add KH560, stir and react at 70℃ for 2h, filter, wash 3 times with ethanol and 3 times with deionized water, and dry in an oven at 70℃ for 20min to obtain silanized modified zinc powder; the mass ratio of modified zinc powder, deionized water, ethanol and KH560 is 2.7:40:100:1;

[0085] A4. It is prepared by mixing silica-titanium dioxide sol and silanized modified zinc powder at a mass ratio of 1:0.8.

[0086] Comparative Example 3

[0087] The only difference between this comparative example and Example 3 is the preparation of the modified filler, as detailed below:

[0088] The modified filler is prepared by the following steps:

[0089] A1. Zinc powder, nano-zirconia, and sodium carboxymethyl cellulose were mixed and stirred at 1200 r / min for 40 min. The mixture was then heated to 310℃ and stirred for another 30 min. After cooling to room temperature, the mixture was washed three times with deionized water and dried in an oven at 70℃ for 30 min to obtain zinc powder-loaded nano-zirconia. The mass ratio of zinc powder, nano-zirconia, and carboxymethyl cellulose was 0.3:1.2:0.02.

[0090] A2. Zinc-loaded nano-zirconia was added to deionized water and ethanol, stirred evenly, KH560 was added, and the mixture was stirred at 70℃ for 2 hours. After filtration, the nano-zirconia was washed three times with ethanol and three times with deionized water, and then dried in an oven at 70℃ for 20 minutes to obtain silanized modified nano-zirconia. The mass ratio of zinc-loaded nano-zirconia, deionized water, ethanol and KH560 was 2.7:40:100:1.

[0091] A3. It is prepared by mixing silica-titanium dioxide sol and silanized modified nano-zirconia at a mass ratio of 1:0.8.

[0092] Comparative Example 4

[0093] The only difference between this comparative example and Example 3 is the preparation of the modified filler, as detailed below:

[0094] The modified filler is prepared by the following steps:

[0095] A1. Zinc powder, nano-zirconia, and sodium carboxymethyl cellulose were mixed and stirred at 1200 r / min for 40 min. The mixture was then heated to 310℃ and stirred for another 30 min. After cooling to room temperature, the mixture was washed three times with deionized water and dried in an oven at 70℃ for 30 min to obtain zinc powder-loaded nano-zirconia. The mass ratio of zinc powder, nano-zirconia, and carboxymethyl cellulose was 0.3:1.2:0.02.

[0096] A2. Zinc-loaded nano-zirconia was placed in a phosphate solution with a pH of 3-4 and sonicated at 50 kHz for 15 min. After filtration, it was washed with deionized water until the pH of the washing solution was neutral and dried in an oven at 80 ℃ for 30 min to obtain modified nano-zirconia. The mass ratio of zinc-loaded nano-zirconia to phosphate solution was 1:8.

[0097] A3. It is prepared by mixing silica-titanium dioxide sol and modified nano-zirconia at a mass ratio of 1:0.8.

[0098] Comparative Example 5 replaced silica-titanium dioxide sol with silica sol.

[0099] The only difference between this comparative example and Example 3 is the preparation of the modified filler, as detailed below:

[0100] The modified filler is prepared by the following steps:

[0101] A1. Zinc powder, nano-zirconia, and sodium carboxymethyl cellulose were mixed and stirred at 1200 r / min for 40 min. The mixture was then heated to 310℃ and stirred for another 30 min. After cooling to room temperature, the mixture was washed three times with deionized water and dried in an oven at 70℃ for 30 min to obtain zinc powder-loaded nano-zirconia. The mass ratio of zinc powder, nano-zirconia, and carboxymethyl cellulose was 0.3:1.2:0.02.

[0102] A2. Zinc-loaded nano-zirconia was placed in a phosphate solution with a pH of 3-4 and sonicated at 50 kHz for 15 min. After filtration, it was washed with deionized water until the pH of the washing solution was neutral and dried in an oven at 80 ℃ for 30 min to obtain modified nano-zirconia. The mass ratio of zinc-loaded nano-zirconia to phosphate solution was 1:8.

[0103] A3. Modified nano-zirconia was added to deionized water and ethanol, stirred evenly, KH560 was added, and the mixture was stirred and reacted at 70℃ for 2 hours. After filtration, the mixture was washed three times with ethanol and three times with deionized water, and dried in an oven at 70℃ for 20 minutes to obtain silanized modified nano-zirconia. The mass ratio of modified nano-zirconia, deionized water, ethanol and KH560 was 2.7:40:100:1.

[0104] A4. It is prepared by mixing silica sol and silanized modified nano-zirconia at a mass ratio of 1:0.8.

[0105] Comparative Example 6 replaced silica-titanium dioxide sol with titanium dioxide sol.

[0106] The only difference between this comparative example and Example 3 is the preparation of the modified filler, as detailed below:

[0107] The modified filler is prepared by the following steps:

[0108] A1. Zinc powder, nano-zirconia, and sodium carboxymethyl cellulose were mixed and stirred at 1200 r / min for 40 min. The mixture was then heated to 310℃ and stirred for another 30 min. After cooling to room temperature, the mixture was washed three times with deionized water and dried in an oven at 70℃ for 30 min to obtain zinc powder-loaded nano-zirconia. The mass ratio of zinc powder, nano-zirconia, and carboxymethyl cellulose was 0.3:1.2:0.02.

[0109] A2. Zinc-loaded nano-zirconia was placed in a phosphate solution with a pH of 3-4 and sonicated at 50 kHz for 15 min. After filtration, it was washed with deionized water until the pH of the washing solution was neutral and dried in an oven at 80 ℃ for 30 min to obtain modified nano-zirconia. The mass ratio of zinc-loaded nano-zirconia to phosphate solution was 1:8.

[0110] A3. Modified nano-zirconia was added to deionized water and ethanol, stirred evenly, KH560 was added, and the mixture was stirred and reacted at 70℃ for 2 hours. After filtration, the mixture was washed three times with ethanol and three times with deionized water, and dried in an oven at 70℃ for 20 minutes to obtain silanized modified nano-zirconia. The mass ratio of modified nano-zirconia, deionized water, ethanol and KH560 was 2.7:40:100:1.

[0111] A4. It is prepared by mixing titanium dioxide sol and silanized modified nano-zirconia at a mass ratio of 1:0.8.

[0112] The performance of the fluorine-free environmentally friendly ceramic non-stick coatings prepared in Examples 1-3 and Comparative Examples 1-6 was tested.

[0113] The above-prepared fluorine-free environmentally friendly ceramic non-stick coating is sprayed onto the substrate surface using a pneumatic spraying method, with the coating thickness controlled at 30-40 micrometers. Then, it is baked at 280℃±50℃ for 15-30 minutes and naturally cooled to room temperature to obtain the coating.

[0114] The hardness of the coating was tested according to GB / T6739-2022 standard, and the adhesion rating of the coating was tested according to ISO4624:2023 standard.

[0115] The coating was immersed in a 5% NaCl solution and a 5% NaOH solution for 1000 hours at a test temperature of 35℃. After immersion, the coating was removed and dried. The hardness of the coating was tested according to GB / T6739-2022 standard, and the adhesion grade of the coating was tested according to ISO4624:2023 standard.

[0116] Coating Abrasion Resistance and Non-stick Test Method: Place the frying pan on the abrasion tester, set the frequency to 33 times / min, apply a downward force of 15N, and use a scouring pad (3M 7447B) with a length of 70±5mm and a width of 30±5mm to move back and forth 100mm as one cycle of friction. After every 500 cycles of friction, clean the pan and perform an egg non-stick test to evaluate the non-stick performance. A non-stick performance of Grade II or above is considered a completed cycle. Replace the scouring pad and begin the next 500 cycles of friction, then clean the pan again and perform the egg non-stick test to evaluate the non-stick performance. Repeat this test until the non-stick performance can no longer reach Grade II standard, then end the test and record the number of cycles.

[0117] Saltwater non-stick coating test method: Prepare a 5% salt solution using purified water, boil for 2 hours, then discard the solution. Perform an egg non-stick test to evaluate the non-stick properties. A non-stick performance of Grade II or higher is considered a completed cycle. Repeat the test until the non-stick performance can no longer reach Grade II, then end the test and record the number of cycles.

[0118] Detergent resistance non-stick test method for coating: Prepare a 2% detergent powder solution using purified water, keep it at 80℃ for 1 hour, then discard the solution, rinse thoroughly with clean water, and then perform an egg non-stick test to evaluate the non-stick performance. A non-stick performance of Grade II or higher is considered a completed cycle. Repeat the test until the non-stick performance can no longer reach Grade II, then end the test and record the number of cycles.

[0119] As shown in Table 1 below.

[0120] Table 1 Performance testing of the fluorine-free environmentally friendly ceramic non-stick coatings prepared in Examples 1-3 and Comparative Examples 1-4

[0121]

[0122]

[0123] Table 2 Performance testing of fluorine-free environmentally friendly ceramic non-stick coatings prepared in Examples 1-3 and Comparative Examples 1-4

[0124]

[0125] As can be seen from the data in Table 1, the fluorine-free environmentally friendly ceramic non-stick coatings prepared in Examples 1-3 have excellent wear resistance, non-stick properties, corrosion resistance, and hardness.

[0126] Comparative Example 1 replaced the zinc powder-loaded nano-zirconia with nano-zirconia, and Comparative Example 2 replaced the zinc powder-loaded nano-zirconia with zinc powder. When these modified fillers were added to a fluorine-free environmentally friendly ceramic non-stick coating, their performance decreased. This proves that the zinc powder is adhered to the surface of the nano-zirconia by sodium carboxymethyl cellulose. After acidification, core-shell nanoparticles with zirconia as the core and zinc powder as the shell are formed, realizing the composite of wear-resistant zirconia and anti-corrosion zinc powder particles. The two phases are uniformly dispersed in the coating, taking into account both high wear resistance and long-term anti-corrosion performance. Moreover, the zinc powder is attached to the zirconia skeleton by sodium carboxymethyl cellulose and is not easy to fall off during friction, thus maintaining the anti-corrosion effect for a long time.

[0127] Comparative Example 3 showed that when modified nano-zirconia was replaced with zinc-loaded nano-zirconia, the modified filler was added to a fluorine-free environmentally friendly ceramic non-stick coating. The coating's performance decreased, demonstrating that the formation of pores in the zinc powder layer on the zinc-loaded nano-zirconia surface increases the contact area between the modified filler and the coating matrix. This mechanical interlocking between the modified filler and the coating matrix ensures uniform and tight dispersion of the filler in the coating, preventing sedimentation and thus maintaining the coating's wear resistance, non-stick properties, and corrosion resistance.

[0128] Comparative Example 4 showed that when the modified filler prepared by replacing the silanized modified nano-zirconia with modified nano-zirconia was added to the fluorine-free environmentally friendly ceramic non-stick coating, its performance decreased. This proved that the silane coupling agent grafted onto the surface of the modified nano-zirconia to obtain silanized modified nano-zirconia, and the addition of organosilicon groups to the outer layer of the modified nano-zirconia to form an inorganic-organic interface layer, is beneficial for the modified nano-zirconia to be embedded in the silica-titanium dioxide sol system, further improving the dispersibility of the modified nano-zirconia in the coating, and improving the wear resistance, non-stickness and anti-corrosion performance of the coating.

[0129] Comparative Example 5, where silica-titanium dioxide sol was replaced with silica sol, and Comparative Example 6, where silanized modified nano-zirconia was replaced with modified nano-zirconia, were added to a fluorine-free environmentally friendly ceramic non-stick coating. The performance of the coating decreased, demonstrating that the silanized modified nano-zirconia, when embedded in the silica-titanium dioxide sol system, can form a three-dimensional inorganic network with the coating matrix. This reduces internal stress in the coating film, increases its hardness, and allows the coating matrix to penetrate the formed three-dimensional inorganic network structure, creating a mechanical interlock between the modified filler and the coating. This improves the interfacial bonding strength between the modified filler and the coating matrix, reducing the likelihood of filler detachment and powdering during friction, thus improving the coating's wear resistance, non-stick properties, corrosion resistance, and hardness. Furthermore, during sintering, the silica-titanium dioxide sol in the modified filler undergoes further condensation, forming a continuous and integrated inorganic ceramic network, further enhancing the coating's crack resistance. The resulting coating has high density, which improves the coating's wear resistance, non-stick properties, corrosion resistance, and hardness.

[0130] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0131] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

Claims

1. A fluorine-free, environmentally friendly ceramic non-stick coating, characterized in that, The raw materials include the following parts by weight: 50-60 parts silica sol, 25-35 parts methyltrimethoxysilane, 10-15 parts waterborne organosilicon-modified acrylic resin, 10-15 parts modified filler, 3-8 parts hydroxyl silicone oil, 5-10 parts pigments and fillers, 30-40 parts deionized water, 1-2 parts dispersant, and 1-2 parts formic acid; The modified filler is obtained by surface treatment of modified nano-zirconia with a silane coupling agent, followed by mixing with silica-titanium dioxide sol; The modified nano-zirconia is obtained by adhering zinc powder to the surface of nano-zirconia with sodium carboxymethyl cellulose and then acidifying it.

2. The fluorine-free environmentally friendly ceramic non-stick coating according to claim 1, characterized in that, The modified filler is prepared by the following steps: A1. Mix zinc powder, nano-zirconia and sodium carboxymethyl cellulose, stir at 1000-1200 r / min for 30-40 min, heat to 300-310℃, continue stirring for 20-30 min, cool to room temperature, wash and dry to obtain zinc powder-loaded nano-zirconia; A2. Zinc-loaded nano-zirconia was placed in a phosphate solution with a pH of 3-4 and ultrasonically treated at 40-50 kHz for 10-15 min. After filtration, washing, and drying, modified nano-zirconia was obtained. A3. Add the modified nano-zirconia to deionized water and ethanol, stir until homogeneous, add silane coupling agent, stir until the reaction is complete, filter, wash and dry to obtain silanized modified nano-zirconia. A4. It is prepared by mixing silica-titanium dioxide sol and silanized modified nano-zirconia in a mass ratio of 1:(0.5-0.8).

3. The fluorine-free environmentally friendly ceramic non-stick coating according to claim 2, characterized in that, In step A1, the mass ratio of zinc powder, nano-zirconia, and carboxymethyl cellulose is (0.1-0.3):(1-1.2):(0.01-0.02).

4. The fluorine-free environmentally friendly ceramic non-stick coating according to claim 2, characterized in that, In step A2, the mass ratio of the zinc-loaded nano-zirconia to the phosphate solution is 1:(7-8).

5. The fluorine-free environmentally friendly ceramic non-stick coating according to claim 2, characterized in that, In step A3, the mass ratio of the modified nano-zirconia, deionized water, ethanol and silane coupling agent is (2.5-2.7):(30-40):(90-100):(0.8-1).

6. The fluorine-free environmentally friendly ceramic non-stick coating according to claim 1, characterized in that, The water-based silicone-modified acrylic resin has a viscosity of 3500-4000S.

7. The fluorine-free environmentally friendly ceramic non-stick coating according to claim 1, characterized in that, The pigments and fillers are any one of titanium dioxide, iron oxide black, carbon black, and copper chromium black.

8. The fluorine-free environmentally friendly ceramic non-stick coating according to claim 1, characterized in that, The dispersant is an aqueous dispersant, specifically dispersant BYK-2012.

9. A method for preparing a fluorine-free, environmentally friendly ceramic non-stick coating with both corrosion resistance and high hardness as described in any one of claims 1-8, characterized in that, The preparation steps include the following: S1. Mix silica sol, methyltrimethoxysilane, waterborne organosilicon-modified acrylic resin, modified filler, pigments and fillers, hydroxyl silicone oil, dispersant and deionized water, grind on a grinder, filter, and obtain component A; S2. Mix component A and formic acid, and carry out a curing reaction at 10-30℃ and 120-180r / min for 6-10h to obtain a fluorine-free environmentally friendly ceramic non-stick coating.